2006
DOI: 10.1002/ijc.21944
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of cyclin A in gastric cancer

Abstract: High level of cyclin A promotes carcinogenesis, and overexpression of cyclin A has been associated with poor prognosis of cancer patients. We validated the prognostic role of cyclin A in gastric cancer and evaluated its correlation with expression of an mRNA stability factor HuR. From 342 consecutive histologically confirmed gastric cancer patients were obtained 325 representative tissue specimens for cyclin A and 316 for HuR immunohistochemistry. Specimens were stained by cyclin A and HuR specific monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
2
40
1
Order By: Relevance
“…Expression of cyclin A has been strongly implicated in the control of cell proliferation and prognoses in human cancers (31)(32)(33). These findings are complementary to ours and suggest that downregulation of SOX6 would favor tumor progression.…”
Section: Discussionsupporting
confidence: 84%
“…Expression of cyclin A has been strongly implicated in the control of cell proliferation and prognoses in human cancers (31)(32)(33). These findings are complementary to ours and suggest that downregulation of SOX6 would favor tumor progression.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast to previous studies (3,17,18,31) that have suggested that the overexpression of cyclin T1 is a poor prognostic factor, our results indicate that low cyclin T1 expression is a poor prognostic factor in treating stomach adeno carcinoma. Patterns of CDK9 and cyclin T1 expression were observed to be similar in normal organ tissue, yet quite different in other tissues (5).…”
Section: Discussioncontrasting
confidence: 99%
“…The overexpression of cyclin E has been considered alternatively as a favorable, poor and irrelevant prognostic factor in clinical outcome (16). Cyclin A may be activated during the transition from the G1 to the S phase of the cell cycle (17,18). Cyclin B1 regulates cell progression through the G2 and M phase.…”
Section: Introductionmentioning
confidence: 99%
“…Normal expression of periplakin would suppress tumor progression; however, when altered, it would allow cancer cells to grow, detach, invade, and gain access to vascular and lymphatic systems. Overexpression of cyclin A2 has been reported in various malignant tumors, including UCB (Chao et al, 1998;Dobashi et al, 1998;Mrena et al, 2006;Sun et al, 2011). Cyclin A2-induced cisplatin resistance is reflected by the suppression of drug-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%